تأثير العوامل البيئية المختلفة على نتائج اختبارات التحسس الجلدية عند مرضى الربو القصبي والتهاب الأنف التحسسي - سلمان, حسين (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة على 473 مريضاً ممن راجعونا في الفترة بين العامين 2000 و 2006 ، والذين شكوا من أعراض أنفية و / أو صدرية. وزع هؤلاء المرضى في ثلاث مجموعات : المجموعة الأولى 183 مريضاً من سكان المدن الساحلية الأصليين، والثانية 152 مريضاً من سكان المدن الساحلية غير الأصليين، أما المجموعة الثالثة فضمت 138 مريضاً من سكان المناطق الجبلية التي يزيد ارتفاعها عن 800 متر عن سطح البحر ( 800 – 1400 متر ). أجريت لجميع هؤلاء المرضى اختبارات التحسس الجلدية التي كانت إيجابية ( تحسس من عامل محسس واحد على الأقل ) عند 61,6 % من هؤلاء المرضى وسلبية عند 38,4 % مع نسب متقاربة في جميع هذه الفئات. بلغت أكبر نسبة تحسس من العت المنزلي في المجموعة الأولى 79,7 % مقابل 68,2 % في المجموعة الثانية و 35,3 % في المجموعة الثالثة، وذلك على عكس نتائج التحسس من غبار الطلع الذي بلغت أكبر نسبة له في المجموعة الثالثة 68,2 % مقابل 48,2 % في المجموعة الثانية و 37,6 % في المجموعة الأولى. في المجموعة الأولى ( حيث أكبر نسبة تحسس من العت المنزلي ) بلغت نسبة مرضى الربو التحسسي 76, 7 %، ومرضى التهاب الأنف التحسسي 23,3 %، أما أكبر نسبة لمرضى التهاب الأنف التحسسي فكانت في المجموعة الثالثة 64,7% ( حيث أكبر نسبة تحسس من غبار الطلع )، مقابل نسبة لمرضى الربو التحسسي بلغت 35,3 % ، أما نتائج المجموعة الثانية فكانت قريبة من نتائج المجموعة الأولى. This study was carried out on 473 patients who consulted us between 2000 and 20006, suffering from nasal and/or chest symptoms. Those patients were divided into three groups. The first group included 183 patients of the local inhabitants of coastal cities. The second included 152 patients of the non-local inhabitants of coastal cities, while the third group included 138 patients of the mountainous areas, higher than 800 meters above sea level (800–1400 meters). An allergic-skin-prick-test was done for all those patients, and the results were positive (allergy being due to at least one allergic factor) at 61.6% of those patients and negative at 38.4%, with converging ratios in all these categories. The highest ratio of the allergy due to the house dust-mite in the first group was 79.7% versus 68.2% in the second group, and 35.3% in the third group. This contradicts the allergy caused by pollen which reached the highest ratio in the third group 68.2% versus 48.2% in the second group, and 37.6% in the first group. In the first group (where the highest ratio of the allergy was due to the house dust-mite), the ratio of the asthma patients was 76.7% and the rhinitis patients 23.3%, but the highest ratio of the patients of rhinitis was 64.7% in the third group (where the highest ratio of allergy being caused by pollen) versus 35.3% of the ratio of the asthma patients; the results of the second group were close to the first group ones.